The SenseCam as a research tool for exploring learner experiences in an urban classroom space - Carmel Chetty (Perspectives in Education, 2015)
In this article1 I describe an ethnographic exploration into the daily school life of Grade 6 learners at an urban school that serves impoverished areas in Durban. The school is representative of the racial demographics of the country. The study explores how Grade 6 learners experience education, and probes how human experiences are mediated through everyday classroom practices and interaction, taking into account the complex influences from the community in the life of the school and, in particular, the lives of the learners. Photographic evidence obtained through the use of a discreet SenseCam, worn by the class teachers and by me, the researcher, in turn, is an essential part of the large data collection that also includes observation notes, interviews, and historical records. I explain the use and value of the SenseCam as a research tool. I demonstrate that learners undermined their own learning and that a multiplicity of factors had an impact on learning and the way the learners experienced school life. Complex social relationships extended beyond the confines of the school.